The Youthful Nation and the Digital Ceiling: Examining the Paradox of EdTech Adoption amidst Systemic Capacity Gaps in Ethiopia - Belay Sitotaw Goshu; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2026)
Ethiopia's demographic surge, with 70% of its 135.5 million citizens under the age of 30, creates unprecedented pressure on an education system already grappling with profound learning poverty and infrastructure deficits. This paper examines the paradox of educational technology (EdTech) adoption amidst these systemic capacity gaps, introducing the "digital ceiling" as a metaphor for the layered structural barriers that constrain digital transformation. Despite ambitious policy frameworks, including Digital Ethiopia 2025/2030 and a comprehensive Digital Education Strategy, the Global Education Futures Readiness Index places Ethiopia in the 10th percentile globally, with critical deficits across infrastructure (8th percentile), human capital, and governance. While homegrown innovations like GlobeDock Academy, Zegju, and the E-School platform have demonstrated remarkable ingenuity, reaching hundreds of thousands of learners through offline-first designs; they confront persistent bottlenecks. Unreliable electricity and connectivity, minimal teacher digital readiness, prohibitive economic exclusion, and institutional fragmentation trap these promising solutions in pilot phases. Without shared operating frameworks and coordinated policy execution, proven innovations fail to integrate into the public school system, risking the erosion of homegrown talent and the exacerbation of urban-rural and gender inequities. This paper argues that Ethiopia's demographic dividend risks becoming a demographic burden unless the nation pursues systemic, sustained investment. Pathways forward require foundational infrastructure expansion, continuous teacher professional development, coherent multi-stakeholder policy alignment, and equity-centered design explicitly targeting rural, low-income, and female learners. Ultimately, dismantling the digital ceiling demands more than deploying devices; it necessitates an aligned ecosystem of capital, capacity, regulatory support, and institutional commitment to transform demographic pressure into a springboard for inclusive and sustainable educational transformation.